2013
DOI: 10.3748/wjg.v19.i40.6888
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between interleukin-6 polymorphism and susceptibility to chronic hepatitis B virus infection

Abstract: The four tag SNPs of IL-6 gene may be associated with susceptibility to chronic HBV infection in the Han Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…IL-6 also induces an inhibitory effect on HBV replication [41]. In addition, IL-6 polymorphisms have been shown to have a close relationship to HBV infection [42]. Therefore, in this section, we focused on the influence of IL-6 and its polymorphisms on HBV infection.…”
Section: Effects Of Il-6 On Hepatitis B Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 also induces an inhibitory effect on HBV replication [41]. In addition, IL-6 polymorphisms have been shown to have a close relationship to HBV infection [42]. Therefore, in this section, we focused on the influence of IL-6 and its polymorphisms on HBV infection.…”
Section: Effects Of Il-6 On Hepatitis B Infectionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) play a role in causing the diversity of HBV clinical courses. Recent studies have demonstrated that IL-6 polymorphisms are involved with chronic HBV infection progression [42].…”
Section: Relationship Between Il-6 Polymorphisms and The Development mentioning
confidence: 99%
“…Previous genetic association studies have reported a protective effect of the A allele in rs2069837 in late-onset Alzheimer's disease, cervical cancer, chronic hepatitis B virus infection, colorectal cancer, and hepatocellular carcinoma (11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…The Takayasu arteritis associated risk allele in this variant is associated with longevity, spastic tetraplegia, cerebral palsy, and antipsychotic-induced weight gain (7)(8)(9)(10). In contrast, the Takayasu arteritis risk allele in rs2069837 was shown to be protective against late-onset Alzheimer's disease, cervical cancer, chronic hepatitis B virus infection, colorectal cancer, and hepatocellular carcinoma (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 95%
“…This pattern of response to environmental stimuli has been suggested to be genetically influenced and may predispose to chronic inflammatory disorders, as demonstrated by Fishman et al (15). The IL6 gene has been associated with many conditions, such as acute coronary syndrome (16) and end-stage renal disease (17), and with susceptibility to infection with chronic hepatitis B virus (18). Strong evidence indicates that the risk of developing periodontitis, as well as the age at onset of periodontitis and its severity, are affected by genetic and environmental factors (19).…”
mentioning
confidence: 99%